Optimal Performance Enhancement Using JIT Manufacturing System Simulation Model - Ezema, Chukwuedozie N.; Nonum, Ernest O.; Umezinwa, Chukwuebuka N.; Igwe, Jerome I. (International Journal of Technology and Systems, 2016)
JIT Manufacturing System is a suitable means for a company that wants to perform in a competitive market This study used a simulation modeling methodology to design a JIT system for drug process plant. It equally examined the impact of different manufacturing system alternatives, manufacturing overhead levels, and product mix complexity levels on manufacturing performance measures. The manufacturing performance measures examined included internal and external as well as financial and non-financial measures of success. These measures were demand fulfillment rate, cycle time, and net operating income. In order to develop a more realistic model by containing other items or more complex factors, other Kanban items and non-Kanban items are included together with the trial item as well as factors that are significant to the operation of the system such as arrival time, batch sizes or waiting time. Not all items produced by the Drug Process Plant were simulated due to software limitation and the scope of the study. Four major items covering 54% of the total order that place the four highest ranks in terms of values are selected for the simulation. The results present particularly interesting implications for manufacturing systems. The increase of demand for more complex and higher priced products presents an opportunity for increased revenues. Higher levels of manufacturing overhead had no significant effect on the product mix decision; however, total costs and differences between the various manufacturing system alternatives are improved. As the manufacturing overhead level setting increases, the slope of the cumulative net operating income curve decreases. The implication for both management and engineers is that the choice of manufacturing system alternative becomes increasingly important as product mix complexity increases and may be amplified as manufacturing overhead levels increase. Material Resource Planning System (MRP) begins to significantly outperform the other two manufacturing system alternatives at a medium demand setting for product mix complexity. This difference becomes more pronounced as product mix complexity is set at a high level. At this high setting, Just in Time Manufacturing System (JIT) begins to slowly outperform Mass Production System (MPS).